Facile method of synthesis of cobalt oxide nanoparticles for formation of supercapacitor electrodes with high specific capacitance - Kalkozova, Ж.К.; Migunova, А.А.; Serikkanov, А.С.; Abdullin, Х.А. (Recent Contributions to Physics, 2024)
Electrochemical energy storage systems have a wide range of applications, including large-scale storage of energy generated by alternative green energy, as well as in electric vehicles and portable electronics. For the operation of electrochemical energy storage systems, supercapacitors play an important role in protecting such systems from failure during power surges. Hybrid metal oxide supercapacitors, particularly those based on cobalt oxide, are promising devices and are intensively investigated. In the present work, a simple method for synthesizing cobalt oxide nanoparticles to form supercapacitor electrodes with high specific capacitance is developed. The method includes synthesis of metastable Zn-Co-O solid solution as an intermediate material. The specific capacitance of the obtained 1 cm2 electrodes was 467.8 F g-1 in CV characteristic measurement and scan rate of 3 mV s-1, 379 F g-1 in GCD method at discharge current of 1 A g-1 and 415 F g-1 in EIS measurement at 0.01 Hz.